Nutritional Approaches of University Students During the COVID-19 Pandemic - Karakoç, Önder (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate nutritional approaches in university students during the COVID-19 pandemic. Methods: A total of 579 university students (male: 296, female: 283) participated in the study. Besides the personal form, the students filled out a nutrition approach testing questionnaire. Students participated voluntarily. The surveys were conducted on social media. Independent sample t and one-way analysis of variance (ANOVA) were applied to analyze the difference in groups. Results: Nutrition scores on the days of curfew (Lockdown) and the days when there is no prohibition or restriction did not change according to gender (p>0.05). A significant difference was found in the nutrition scores of the students according to the levels they felt on the days when there was a curfew and, on the days, when there was no prohibition or restriction (p<0.05). A significant difference was found between the scores of the students of different faculties on the days when there was a curfew and, on the days, when there was no prohibition or restriction (p<0.05). Conclusion: It has been determined that the nutritional habits of university students do not change according to gender in the event of prohibition and restriction or not during the coronavirus epidemic. While the nutritional habits of university students were similar according to gender, it was found that they changed according to the type of faculty. The nutritional habits of the faculty students who received education on health were found to be better. Those who feel bad have lower nutritional scores. During the coronavirus epidemic, it is recommended to provide psychological assistance to students in support of nutrition, whether there are curfews, bans, or days when there is no ban.